An Exploration of the Cultural Significance of Traditional Foods in Rural Punjab: A Qualitative Study - Irshad Mohsin; Maria Akram; Iram Iqbal (Dialogue Social Science Review (DSSR), 2025)
The present research study discovers the cultural significance of the traditional foods in rural areas of Punjab, Pakistan through qualitative lens as the food practices in rural areas of Punjab are deeply knotted with the region’s agricultural traditions, the community life and cultural heritage. The main focus of this research is on understanding how traditional foods contribute to shaping local identities, fostering social cohesion and reinforcing the agricultural ties. The data were collected by semi-structured interviews and the participant observation in a rural village reflecting the preparation, consumption and the communal aspects of the food. Findings of the study reveal that food is not only a means of sustenance but a vital cultural tool that connects people to their heritage in rural Punjab. The themes identified including the preservation of cultural identity through food, role of food in maintaining social bonds and the significance of food in marking religious and cultural rituals. This study also highlights the economic connection between food practices and the local agriculture, depicting how seasonal ingredients shape meal preparation. The research emphasizes the significance of traditional food as a means of cultural expression and community unity in rural Punjab suggesting that food plays a vital role in sustaining both individual and collective cultural identities. Key words: The traditional foods, cultural significance, community bonding, agricultural practices, rural Punjab, cultural identity, qualitative study, Punjabi cuisine, food heritage, food practices.